Laboratory assessment of coagulation - Salvagno, Gian Luca (Henry Stewart Talks, 2026)
Blood test, Sampling issues, Blood sample management, Errors in laboratory analysis caused by blood clotting, Sample processing time, Factors affecting blood sample analysis, Hemostasis assays